2006
DOI: 10.1007/s11064-006-9195-7
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-induced Proteolysis After Transient Global Cerebral Ischemia and Ischemic Tolerance in a Rat Model

Abstract: The activation of the [Ca(2+)]-dependent cysteine protease calpain plays an important role in ischemic injury. Here, the levels of two calpain-specific substrates, p35 protein and eukaryotic initiation factor 4G (eIF4G), as well as its physiological regulator calpastatin, were investigated in a rat model of transient global cerebral ischemia with or without ischemic tolerance (IT). Extracts of the cerebral cortex, whole hippocampus and hippocampal subregions after 30 min of ischemia and different reperfusion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
3
4
1
Order By: Relevance
“…Our results are in agreement with research showing that ischaemic tolerance, which promotes translation recovery, tends to prevent eIF4G processing and to favour the phosphorylation of 4E-BP1 [47,50].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with research showing that ischaemic tolerance, which promotes translation recovery, tends to prevent eIF4G processing and to favour the phosphorylation of 4E-BP1 [47,50].…”
Section: Discussionsupporting
confidence: 93%
“…rats subjected to transient forebrain ischemia. We and other groups have previously demonstrated the involvement of p25 in this model (Garcia-Bonilla et al, 2006; Wang et al, 2003; Wen et al, 2007). Also, p25 is upregulated in human postmortem brains following ischemic stroke (Mitsios et al, 2007).…”
Section: Resultssupporting
confidence: 68%
“…Previous studies have indicated that the intracellular effects of ischemia include the activation of calpains, a family of calcium-activated cysteine proteases which trigger substrate-specific proteolysis that may contribute to neuronal death [21], after both in vivo [22], [23] and in vitro ischemia [24][26]. Calpain activation (usually detected as the breakdown products of a preferred substrate, spectrin) can therefore serve as an indirect indicator of the induction of cell death.…”
Section: Resultsmentioning
confidence: 99%